Genetic diversity and population structure of Philippine strawberry germplasm based on genome-wide simple sequence repeat markers - VENUS H. ELEC; CHARLES ANTHON E. CADORNA; BELINDA A. TAD-AWAN; DARWIN A. BASQUIAL; MILAGROS R. DUMASLAN; JESSICA D. REY (Society for Indonesian Biodiversity, 2024)
Abstract. Elec VH, Cadorna CAE, Tad-Awan BA, Basquial DA, Dumaslan MR, Rey JD. 2024. Genetic diversity and population structure of Philippine strawberry germplasm based on genome-wide simple sequence repeat markers. Biodiversitas 25: 2969-2979. Strawberry is a globally recognized fruit due to its health benefits and economic significance. Determining the level of genetic diversity and the relationship between germplasm resources involved in the breeding program is critical for effective crop improvement strategies. This study used 197 Simple Sequence Repeat (SSR) markers to assess the genetic diversity and population structure of 24 strawberry germplasm from the Benguet State University (BSU) collection. In this study, 70% of the markers used were polymorphic with reproducible fragments. A total of 792 alleles were detected, with an average of six per marker. The diversity indices indicated an intermediate level of diversity among the germplasm based on the Jaccard coefficient. Results from cluster analysis generated three groups, separating the Red Milky Way and Summer Princess cultivars from the rest of the germplasm evaluated, while a third cluster was further divided into six subgroups. Furthermore, identified clustering patterns of the evaluated genotypes showed independence from the region of origin, coinciding with Principal Component Analysis (PCA) and population structure analysis results. This study reveals the genetic diversity level and population structure of the strawberry cultivars in the Philippines using SSR markers, facilitating accurate identification and informed parental selection for breeding objectives.